Composition of Polyphenols and Antioxidant Activity of Garlic Bulbs Collected from Different Locations of Korea - Nagella, Praveen; Thiruvengadam, Muthu; Ahmad, Ateeque; Yoon, Jae-Yeon; Chung, Ill-Min (Asian Journal of Chemistry, 2014)
The aqueous extracts of garlic bulbs collected from different locations of Korea viz., Namdo, Daeso, Godang, Hampyeong and Sangeol were analyzed for their phenolic profiles and screened for their antioxidant activities. Antioxidant activity was evaluated by four different methods namely DPPH radical scavenging activity, reducing power assay, metal chelating activity and phosphomolybdenum activity. Spectrophotometric analysis revealed that the highest levels of total phenolic content and total flavonoid content were found in the garlic bulbs collected from Hampyeong region. A total of 23 polyphenolic compounds were identified and quantified from garlic bulbs, including hydroxybenzoic acids, hydroxycinnamic acids, flavonols and other groups of phenolic compounds. The ultra performance liquid chromatography (UPLC) analysis of the phenolic compounds profile revealed that b-resorcylic acid was the dominant phenolic compound found in garlic bulb extracts collected from different locations; it constituted about 313.50 μg/g from Sangeol region to 452.10 μg/g from Godang region, followed by pyrogallol (139.35 to 418.80 μg/g), gallic acid (67.40 to 196.80 μg/g), rutin (51.35 to 90.45 μg/g), protocatechuic acid (31.75 to 76.25 μg/g) and quercetin (25.70 to 56.65 μg/g). The garlic bulbs collected from the Hampyeong region exhibited highest antioxidant activity assayed by four different methods except the phosphomolybdenum assay when compared with other garlic bulbs of different locations.